Potensi Limbah Cangkang Kerang sebagai Kerajinan Sederhana Rumah Tangga di Desa Jampue Kecamatan Lanrisang Kabupaten Pinrang - Yunus, Yusdalifa Ekayanti; Yamin, Mayasari; Gau, Andi Dita Tawakkal; Zamzam, Syamsiar; Yunus, Muhammad Yusuf; Irwandi, Adi (Hippocampus: Jurnal Pengabdian Kepada Masyarakat, 2023)
The use of local materials in the creative industry is now leading to a global economic market. This also had an impact on the women in the Jampue Village PKK who used shell waste as a household-scale craft industry. This service activity aims to educate PKK women in Jampue Village to be more creative in utilizing shell waste as a mainstay product that can compete in the international market. The stages of implementation carried out are by means of socialization and workshops regarding the procedures for making and selecting shells that have the potential to be used as household scale crafts. The implementation of this mentoring program was able to increase the understanding of PKK women in Jampue Village regarding the potential of shell waste which can be used as crafts.